SEJARAH PERADABAN DAN MASA DEPAN KESADARAN MANUSIA PADA POSISI ONTOLOGIS KECERDASAN BUATAN (ARTIFICIAL INTELLIGENCE) DALAM PERSPEKTIF ALQURAN: (Kajian Tafsir Ayat-Ayat Filosofis) - Pohan, Zulfikar Riza Hariz; Idris, Muhd. Nu’man; Ramli, Ramli; Anwar, Anwar; Paisal, Jon (BASHA'IR: JURNAL STUDI AL-QUR'AN DAN TAFSIR, 2023)
Artificial intelligence (AI) can now be found easily in various aspects of human life ranging from computer programs, vehicles and devices. This for some people is quite worrying, but there are also those who consider it as an advance of civilization. AI, which initially only revolved around industrial technological advances, now doubles as part of ontological discussions, especially themes of consciousness. The intelligence possessed by AI in simulating is undoubted, especially with the existence of chatbots and algorithms. However, since its inception, AI has always been faced with the concept of consciousness. Consciousness is an abstract thing, because it is believed to be possessed only by humans. AI itself is considered to have a large content in human civilization and the future history of human civilization. In the verses of the Qur'an, human life is not a simulation, and consciousness is immaterial, and cannot be captured by science. Thus, AI can only be positioned as an instrument, which cannot achieve the status of having consciousness ontologically. AI is not value-free, technology in history has often been used to oppress humans and AI is considered potentially a disaster for humanity. This research is sourced from the literature study approach in finding data related to technological advances and the responses that surround them. This research is expected to be able to contribute new knowledge in terms of Quranic studies, history, technology and science.